2016
DOI: 10.18052/www.scipress.com/ilns.51.63
|View full text |Cite
|
Sign up to set email alerts
|

Population and Nesting Records of House Sparrow <i>Passer domesticus </i> in Yellampet, Nizamabad District, Telangana, India

Abstract: ABSTRACT. Studied the population and nesting records of House Sparrow Passer domesticus during winter in Yellampet village, Telangana. The ecological density of House Sparrow was investigated using fixed width transects. The density of sparrow vary from 15 to 335 per hectare in different transects. Bonferroni confidence interval was used to know the preference of location types i.e., houses, shops and hotels for foraging and nesting. Shops were used significantly more than expected according to availability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In the current study, house type did not generally have an impact on the higher number of active nests in some areas, whereas in 2016 the number of active nests was related to traditional house type. This indicated that House Sparrows do not exclusively rely on house type availability to nest, but any suitable nesting space available at the time as in other studies (Narayana 2016;Reynolds et al 2019).…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…In the current study, house type did not generally have an impact on the higher number of active nests in some areas, whereas in 2016 the number of active nests was related to traditional house type. This indicated that House Sparrows do not exclusively rely on house type availability to nest, but any suitable nesting space available at the time as in other studies (Narayana 2016;Reynolds et al 2019).…”
Section: Discussionmentioning
confidence: 54%
“…In the current study, factors like availability of active nests played a role in the number of the House Sparrow in some of the areas; as a result, this may implicate potential increment to the numbers of the House Sparrow in these areas. The presence of active nests has been reported to be positively linked to reproduction success (Peach et al 2008), and the colonisation rate of House Sparrows (Narayana 2016), which can result in relatively large impacts as they are implicated in facilitating transmittable diseases, e.g., in Nebraska a large number of active nests were affected by the Buggy Creek Virus (O'Brien and Brown 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations